Understanding & Designing Marketing Research - Webb John R (The Dryden Press, 1999)
An introduction to array of techniques which is known collectively as Marketing Research. Preface, Research for Marketing, The Process of Research, Secondary Data - Uses and Limitations, The Process of Sampling, Survey and Panel/ Syndicated Research, Questionnaire Design, Qualitative Research, Measurement and Scales, Attitudes and Their Measurement, Experimentation, Writing and Reading Research Reports, Commissioning Marketing Research, Statistics and Sampling, Index.